Micro-scale impact testing on cemented carbides. (November 2019) - Cinca, N.; Beake, B.D.; Harris, A.J.; Tarrés, E.
Abstract: Neither hardness nor fracture toughness alone can reliably predict tool performance under repetitive impact testing such as in drilling operations or solid particle impact. WC-Co based alloys are usually classified for the application according to those two properties without much consideration on their resistance to impact fatigue. The aim of the present study is to evaluate the behaviour of three cemented carbide grades used for oil and gas applications under micro-scale impact fatigue, two of them having similar hardness and toughness values, one with the presence of cubic carbides. In the repetitive micro-impact tests at a load range of 1–3 N with a normalized penetration depth ( h/R ) larger than typical macroimpact tests, it was found that neither the hardest and stiffest grade nor the toughest grade exhibited highest resistance to impact fatigue, but rather the one with the highest H / E and highest H 3 / E 2 ratios, meaning that it shows higher elastic strain to break and resistance to plastic deformation. Examination of the damage showed significant differences in the extent of plastic deformation and crack patterns, being the grade with lower contiguity and higher mean free path, the one with larger degradation on the carbide structure at all examined loads, and the grade with CoNi binder and cubic carbides having lower damage rate. Highlights: Repetitive microimpact indentation tests have been performed on three cemented carbide grades. The highest fatigue sensitivity is found for the grade with lower contiguity and higher mean free path. The highest H / E and highest H 3 / E 2 ratios resulted in better fatigue resistance. Different wear regimes are observed according to the grade feasibility to damage nucleation and propagation.